Sangha Affairs Administration under the Eastern Maha Nikaya, Sangha Administrative Region 9 - Chantasupho, Phraatchaya; Pollaharn, Chumnian; Duangchatom, Kritkanok (Interdisciplinary Academic and Research Journal, 2023)
Buddhism has been the religion of the Thai nation since ancient times, all arts and cultures, traditions, ethics, and virtues that are uniquely Thai, have very important roots in Buddhism. Buddhism is regarded as an invaluable heritage of Thailand. It is a spiritual anchor that causes unity and national security, able to maintain Thainess well all along. The administration of the Sangha in Thailand in the modern era has the Patriarch as the highest authority. The administration of the Sangha in this era is by the Sangha Act B.E. This article aims to analyze the administrative situation of the Eastern Maha Nikaya in the ninth Eastern Maha Nikaya administrative region. The research was divided into three phases as follows; (1) The study of documents aims to bring the results from the study of the Sangha Administration documents as a context for constructing a questionnaire to study the current and desirable conditions in the Sangha administration. (2) An interview with the experts is the use of research results in Step 1 to design a research issue to study the administrative conditions of the clergy. The target group of data is 7 experts. And (3) Analysis of current and desirable conditions. The sample group is 261 monks in Administrative Region 9. Data were analyzed by descriptive statistics, while qualitative data was analyzed by Analytic Inductive. The results showed that; The current state of the Sangha administration as a whole was at the highest level, and the desirable state of the Sangha’s administration as a whole was at the highest level. In descending order of the present state, the highest level is the highest; religious education, followed by government, welfare education, mission, public utilities, and public welfare respectively. And the most desirable state in all aspects, in descending order is; Educational welfare, followed by government, religious education, public utilities, missions, and public welfare, respectively.